Biosynthesis of waxy starch - a review - Evžen ŠÁRKA; Václav DVOŘÁČEK (Plant, Soil and Environment, 2017)
Starch comprises nearly linear amylose and branched amylopectin, whilst waxy starches are a special form, containing almost exclusively amylopectin. Modern techniques in plant breeding together with new data from starch biosynthesis research have enabled new food and non-food uses of waxy starches. This paper describes the basic ways of glucose conversion to waxy starch in plants. The recent evidence of ADP-Glc accumulation in cytosol of photosynthetically competent cells proposes a more complex pathway of starch biosynthesis based on a tight interconnection of sucrose and starch metabolic pathways. Also many studies indicate the existence of different pathways for the sucrose-starch conversion process in heterotrophic organs of dicotyledonous and monocotyledonous plants. At least six classes of starch synthases (SS) have been recognised in plants including soluble SS1, SS2, SS3, SS4, SS5, and granule bound SS (GBSS), required for the synthesis of short and long chains of amylopectin, till now. As to amylose (not-present in waxy starches), GBSS is the only starch synthase isoform encoded by the waxy genes situated at independent loci.